1994
DOI: 10.1021/bi00173a017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That CYP2C19 is the Major (S)-Mephenytoin 4'-Hydroxylase in Humans

Abstract: The present study assesses the role of members of the human CYP2C subfamily in the 4'-hydroxylation of (S)-mephenytoin. When recombinant CYP2C proteins were expressed using a yeast cDNA expression system, 2C19 stereospecifically 4'-hydroxylated (S)-mephenytoin with a turnover number at least 10 times higher than that of human liver microsomes. 2C9 (both Ile359 and Leu359 alleles) and 2C18 (Thr385 and Met385 alleles) metabolized this substrate at a rate 100-fold lower than 2C19, and metabolism by these 2C prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
1
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(154 citation statements)
references
References 42 publications
5
146
1
2
Order By: Relevance
“…mg protein-' (in the case of CYP 2C8), despite the use of identical expression systems (Table 1). Since these cytochromes P-450 have been described to hydroxylate tolbutamide (Brian et al, 1989;Relling et al, 1990;Goldstein, 1994b), this activity was chosen as a control for the metabolic competence of our microsomal fractions. All the expressed cytochromes P-450 2C were able to hydroxylate tolbutamide under standard incubation conditions (Table l), while no activity was detected in microsomes from control yeast.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…mg protein-' (in the case of CYP 2C8), despite the use of identical expression systems (Table 1). Since these cytochromes P-450 have been described to hydroxylate tolbutamide (Brian et al, 1989;Relling et al, 1990;Goldstein, 1994b), this activity was chosen as a control for the metabolic competence of our microsomal fractions. All the expressed cytochromes P-450 2C were able to hydroxylate tolbutamide under standard incubation conditions (Table l), while no activity was detected in microsomes from control yeast.…”
Section: Resultsmentioning
confidence: 99%
“…Saccharornyces cerevisiae strain 334 was used for expression. Details of the protocols for construction of vectors and yeast transformation have been described elsewhere (Kaminsky et al, 1992;Goldstein et al, 1994b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only extensive metabolizers (EM), expressing functional CYP2C19, are able to hydroxylate (S)-mephenytoin to (S)-4´-hydroxymephenytoin, which is subsequently conjugated almost completely to the (S)-4´-hydroxymephenytoin glucuronide and excreted renally. 16,17 In CYP2C19 deficient poor metabolizers (PM), (S)-mephenytoin is biotransformed via slow N-demethylation, which in vitro is preferentially mediated by CYP2B6 (with minor contribution of CYP2C9), resulting in the formation of (S)-nirvanol. [18][19][20] (R)-mephenytoin is preferably demethylated to (R)-nirvanol and hydroxylated only to a small extent.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive metabolizer (EM) and poor metabolizer (PM) polymorphism for mephenytoin [3,4] is well known and has been studied extensively. It has been shown that CYP2C19 is a candidate for mephenytoin 4'-hydroxylation [5,6]. However, the role of CYP2C18 and the relationships between the other CYP2C subfamily members and the CYP2C18 gene have not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%